The basics of radiation damage in crystalline silicon networks by NIEL - Carla Daruich de Souza; Jong Bun KIM; Jin Joo KIM; Jin KIM; Wanook JI; Kwang Jae SON; Sang Mu CHOI; Gu Jin KANG; Jin Te HONG (Brazilian Journal of Radiation Sciences, 2021)
Basically, radiation can cause two effects on materials: ionization and non-ionization. This work presented the theory involved in defects caused by non-ionization, known as NIEL, with a focus on silicon materials. When energy is transferred directly to the atoms in the crystalline lattice, it can either be dissipated in the form of vibrations or be large enough to pull atoms out of that lattice. This weakens the lattice, causing measurement errors that can lead to permanent damage. This study is extremely important because silicon materials are used in radiation detectors. These detectors cannot return false measurements, especially in dangerous situations, such as in nuclear reactor monitoring. After presenting the theory involved, examples are shown. Failures of up to 30% were found by the researchers.